2021
DOI: 10.1177/01617346211035315
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Axillary Lymph Nodes for Metastasis on Ultrasound Using Artificial Intelligence

Abstract: The purpose of this study was to evaluate an artificial intelligence (AI) system for the classification of axillary lymph nodes on ultrasound compared to radiologists. Ultrasound images of 317 axillary lymph nodes from patients referred for ultrasound guided fine needle aspiration or core needle biopsy and corresponding pathology findings were collected. Lymph nodes were classified into benign and malignant groups with histopathological result serving as the reference. Google Cloud AutoML Vision (Mountain View… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In normal LNs, the cortex is usually stiffer than the hilum, and this architecture is generally also preserved in inflammatory LNs. Conversely, malignant carcinoma cells proliferate rapidly and infiltrate the lymph node, distorting the normal architecture and increasing its stiffness [85]. However, focal infiltration may be challenging to detect, and lymphoma may produce soft lymph nodes that can predominantly have similar elasticity to the surrounding tissue, thus representing a specific challenge for this application [7].…”
Section: Lymph Nodesmentioning
confidence: 99%
See 1 more Smart Citation
“…In normal LNs, the cortex is usually stiffer than the hilum, and this architecture is generally also preserved in inflammatory LNs. Conversely, malignant carcinoma cells proliferate rapidly and infiltrate the lymph node, distorting the normal architecture and increasing its stiffness [85]. However, focal infiltration may be challenging to detect, and lymphoma may produce soft lymph nodes that can predominantly have similar elasticity to the surrounding tissue, thus representing a specific challenge for this application [7].…”
Section: Lymph Nodesmentioning
confidence: 99%
“…A study by Tahmasebi et al assessed the accuracy of image classification software (Google Cloud AutoML Vision, Mountain View, CA) compared to three expert radiologists, regarding a dataset containing ultrasound images of 317 axillary lymph nodes, using the histopathology as a reference standard. They showed that AI has comparable performance to expert radiologists and could be used to predict the presence of metastases in ultrasound images of the axillary lymph nodes [85].…”
Section: Lymph Nodesmentioning
confidence: 99%
“…One study compared the performances of Google Cloud AutoML Vision (Mountain View, CA, USA) with the performances of three experienced radiologists [ 38 ]. Ultrasound images of 317 axillary lymph nodes from breast cancer patients were collected.…”
Section: Studies Using Radiomics For Breast Cancer Lymph Node Predictionmentioning
confidence: 99%
“…Ultrasound images of 317 axillary lymph nodes from breast cancer patients were collected. When evaluated on three independent test sets, the AI system achieved better specificity (64.4% vs. 50.1%) and positive predictive value (68.3% vs. 65.4%), while it achieved worse sensitivity (74.0% vs. 89.9%) and comparable accuracy (69.5% vs. 70.1%) ( Table 2 ) [ 38 ]. Hence, this study showed how an automated AI system yields performances similar to that of experienced radiologists.…”
Section: Studies Using Radiomics For Breast Cancer Lymph Node Predictionmentioning
confidence: 99%
“…21,22 Our group investigated the ultrasound-based AI performance in thyroid lesions, lymphatic involvement in breast cancer, and retrospectively in NAFLD. [23][24][25][26] However, relatively few papers have prospectively investigated the performance of AI techniques in assessing liver fat content on using ultrasound. [27][28][29][30] It is hoped that AI can assist physicians in making more accurate and reproducible imaging diagnoses and also reduce physician's workload.…”
mentioning
confidence: 99%